The Influence of Work Discipline, Employee Loyalty, and Work Ability on Employee Performance in Layer Chicken Farming Business at Aura Farm, Lima Puluh Kota Regency, West Sumatra - Siti Azizah; Ila Haque Faura Affandi Siti Azizah (Agriwar Journal, 2025)
The layer poultry farming industry plays a crucial role in food security, particularly in providing eggs as a source of animal protein. In Indonesia, egg production continues to increase, with West Sumatra being one of the central producing regions. Aura Farm, located in Lima Puluh Kota Regency, faces challenges in optimizing employee performance, which is influenced by work discipline, employee loyalty, and workability. This study, conducted from October to November 2024, aims to analyze the impact of work discipline, employee loyalty, and workability on employee performance at Aura Farm. A quantitative method, utilizing multiple linear regression analysis, was employed, and data were collected through questionnaires distributed to all 20 employees. Statistical tests, including validity and reliability checks, as well as classical assumption tests, were performed to ensure data accuracy. The results indicate that work discipline, employee loyalty, and workability have a significant impact on employee performance. High discipline, intense loyalty, and adequate skills contribute positively to productivity. Employees with better discipline, commitment, and abilities perform more efficiently and effectively. Therefore, companies are advised to enhance human resource management by improving discipline, loyalty, and skill development to achieve better productivity.